The plant hormone ethylene promotes abiotic stress tolerance in the liverwort Marchantia polymorpha - Bharadwaj, Priyanka S.; Sanchez, Lizbeth; Li, Dongdong; Enyi, Divine; Van de Poel, Bram; Chang, Caren (Frontiers in Plant Science, 2022)
Plants are often faced with an array of adverse environmental conditions and must respond appropriately to grow and develop. In angiosperms, the plant hormone ethylene is known to play a protective role in responses to abiotic stress. Here we investigated whether ethylene mediates resistance to abiotic stress in the liverwort Marchantia polymorpha, one of the most distant land plant relatives of angiosperms. Using existing M. polymorpha knockout mutants of Mpein3, and Mpctr1, two genes in the ethylene signaling pathway, we examined responses to heat, salinity, nutrient deficiency, and continuous far-red light. The Mpein3 and Mpctr1 mutants were previously shown to confer ethylene insensitivity and constitutive ethylene responses, respectively. Using mild or sub-lethal doses of each stress treatment, we found that Mpctr1 mutants displayed stress resilience similar to or greater than the wild type. In contrast, Mpein3 mutants showed less resilience than the wild type. Consistent with ethylene being a stress hormone, we demonstrated that ethylene production is enhanced by each stress treatment. These results suggest that ethylene plays a role in protectiing against abiotic stress in M. polymorpha, and that ethylene has likely been conserved as a stress hormone since before the evolutionary divergence of bryophytes from the land plant lineage approximately 450 Ma.